GAMBARAN PEMBERIAN MENU SEHAT MPASI DALAM UPAYA PENCEGAHAN STUNTING DI KABUPATEN BIMA - Purnama, Yati; Sulami, Neti (Jurnal Ilmiah Mandala Education (JIME), 2022)
One of the factors can directly affect stunting in children under the age of two is the intake factor, including breast milk (ASI) and complementary foods for breast milk (MPASI). MPASI is food or drink that contains nutrients and is given to infants or children aged 6-24 months to meet nutritional needs other than breast milk. Appropriate complementary feeding is an effort can reduce stunting rates and increase child survival. A good complementary food is fulfilling the requirements on time, nutritionally complete, sufficient and balanced, safe, and given in the right way.This study aims to find out the description of giving a healthy complementary food menu to prevent stunting, the time of giving the first complementary food, the history of breastfeeding, knowing the type of complementary food given to children, knowing the texture of the complementary food given to children and knowing the portion of complementary food each meal.This research is a quantitative research, conducted in Bima, NTB. Data collection techniques were carried out by distributing questionnaires and observations. The data analysis used in this study was univariate.The results showed that most of the toddlers received complementary foods according to the time of administration, namely from the age of 6 months by 75%, most of the respondents were still wrong in determining the texture of complementary foods by 77%, most of the respondents were less precise in the frequency of giving complementary foods by 75%, most of them respondents in terms of the portion of complementary feeding has been appropriate by 59%, some respondents in giving complementary food have not applied the healthy menu of complementary food 4 stars by 73%.